Comparison of acute response of cardiac autonomic modulation between virtual reality-based therapy and cardiovascular rehabilitation: a cluster-randomized crossover trial - Silva, Paula F. [UNESP]; Ricci-Vitor, Ana Laura [UNESP]; Cruz, Mayara M. [UNESP]; Borges, Giovanna L. [UNESP]; Garner, David M.; Marques Vanderlei, Luiz C. [UNESP] (Taylor & Francis, 2020)
Objective: To assess the acute response of cardiac autonomic modulation (ACAM) during and after a session of virtual reality-based therapy (VRBT) compared to a session of conventional cardiovascular rehabilitation (CR) and to evaluate the effects of 12 weeks of training on this response. Methods: We assessed 28 volunteers (63.4 ± 12.5 years). The ACAM was judged by linear indexes of heart rate variability (HRV) in VRBT and CR sessions. Later, patients completed 12 weeks of VRBT+CR and the assessment was repeated at the 12th week. Results: Throughout the 1st VRBT session vagal withdrawal occurred (RMSSD/HFnu); sympathetic nervous system stimulation (LFnu) and progressive decrease of global HRV (SDNN). During the recovery, the SDNN, HFnu, and LFnu improved from the 5thminute on both therapies. After 12 weeks, the LFnu, HFnu, and the LF/HF-ratio revealed no significant changes in Ex3-Ex4 equated to Rep during VRBT. In recovery, the HFnu and LFnu improved before the 5thminute on both therapies. Conclusions: ACAM during and after the VRBT was comparable to CR, yet, the extents were greater in the VRBT. After 12 weeks of VRBT training, the subjects adapted to the exercises from the 15thminute and exhibited faster recovery of HFnu and LFnu indexes compared to the 1st week.
Keywords: Cardiac rehabilitation; cardiovascular diseases; exercise; sympathetic nervous system; virtual reality exposure therapy